2020
DOI: 10.1038/s41598-019-57075-6
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry Imaging of atherosclerosis-affine Gadofluorine following Magnetic Resonance Imaging

Abstract: Molecular imaging of atherosclerosis by Magnetic Resonance Imaging (MRI) has been impaired by a lack of validation of the specific substrate responsible for the molecular imaging signal. We therefore aimed to investigate the additive value of mass spectrometry imaging (MSI) of atherosclerosis-affine Gadofluorine P for molecular MRI of atherosclerotic plaques. Atherosclerotic Ldlr −/− mice were investigated by high-field MRI (7 T) at different time points following injection of atherosclerosis-affine Gadofluori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…In the context of atherosclerosis, recent studies use MSI as a novel strategy to visualize atherosclerotic plaque localization in the aorta of atherosclerotic mice such as LDL receptor knockout (LDLR –/– ) fed a cholesterol-rich diet or apolipoprotein E knockout (ApoE –/– ) mice [ 7 , 31 ], and to evaluate treatment effects on plaque formation and remodelling of the complex lipid components [ 7 ]. These animal studies define several lipid markers for a deeper understanding of the causes and underlying mechanisms of plaque progression.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of atherosclerosis, recent studies use MSI as a novel strategy to visualize atherosclerotic plaque localization in the aorta of atherosclerotic mice such as LDL receptor knockout (LDLR –/– ) fed a cholesterol-rich diet or apolipoprotein E knockout (ApoE –/– ) mice [ 7 , 31 ], and to evaluate treatment effects on plaque formation and remodelling of the complex lipid components [ 7 ]. These animal studies define several lipid markers for a deeper understanding of the causes and underlying mechanisms of plaque progression.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, in-house solid matrix-matched standards were prepared from uranium-spiked kidney homogenate. Nevertheless, further calibration strategies are found in the literature including the solution-based calibration [27], fabrication xerogel solid calibration standards which are more suitable for the calibration of glasses and silicate matrices [28], the synthesis of metal-spiked polymer films [29], the use of dried droplets or dried matrix spots (DMS) deposited on different substrates [30][31][32][33][34], and the spiking and sectioning of gelatine droplets, whose use has increased noticeably in recent years for the quantitative analysis of biological tissues [35][36][37][38][39][40][41]. For internal standardization, three different approaches are mainly described in the literature for the quantitative elemental imaging of biological samples: (i) the simultaneous nebulization of a standard solution [42], (ii) the use of an element naturally occurring in the sample [43][44][45], and (iii) the addition of an internal standard-spiked layer between the sample and support or on the sample [46][47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Woodside et al have visualized overall inflammatory cell burden in different regions of the aorta in ApoE −/− mice at clinically relevant field strengths by using a targeted gadolinium contrast agent binding to the integrin α4β1, which is involved in the recruitment of inflammatory cells to atherosclerotic plaques [ 144 ]. Moreover, a recent study showed gadofluorine P accumulation in aortic atherosclerotic plaques of low density lipoprotein receptor deficient (Ldlr −/− ) mice with MRI, followed by ex vivo mass spectrometry imaging to quantify the contrast agent to validate its local accumulation [ 145 ].…”
Section: Wss and Pwv Interact To Promote Plaque Growth And Vasculamentioning
confidence: 99%